2020
DOI: 10.1302/0301-620x.102b7.bjj-2019-1486.r1
|View full text |Cite|
|
Sign up to set email alerts
|

Outcomes of total hip arthroplasty using dual mobility components in patients with a femoral neck fracture

Abstract: Aims Dislocation is the most common indication for further surgery following total hip arthroplasty (THA) when undertaken in patients with a femoral neck fracture. This study aimed to assess the complication rates of THA with dual mobility components (THA-DMC) following a femoral neck fracture and to compare outcomes between THA-DMC, conventional THA, and hemiarthroplasty (HA). Methods We performed a systematic review of all English language articles on THA-DMC published between 2010 and 2019 in the MEDLINE, E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
47
1
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(53 citation statements)
references
References 58 publications
1
47
1
4
Order By: Relevance
“…This risk could be related to different predisposing conditions observed in FNF patients, such as a good preoperative hip ROM, the prevalence of recurrent falls in older patients or the frequent postoperative delirium that compromises adherence to rehabilitation programs [ 29 , 30 ]. This increased risk is further confirmed by some systematic reviews: the authors of [ 31 ] reported that DMC THA is associated with a significantly lower dislocation rate compared with conventional THA (OR 0.26; 95% CI, 0.08 to 0.79); this was also confirmed by Romagnoli M. et al [ 32 ], who showed a slight significant risk ratio of 0.16 (95% CI, 0.09, 0.28; I 2 = 0%, p -value < 0.00001), with a statistically significant difference between the two groups.…”
Section: Discussionmentioning
confidence: 59%
“…This risk could be related to different predisposing conditions observed in FNF patients, such as a good preoperative hip ROM, the prevalence of recurrent falls in older patients or the frequent postoperative delirium that compromises adherence to rehabilitation programs [ 29 , 30 ]. This increased risk is further confirmed by some systematic reviews: the authors of [ 31 ] reported that DMC THA is associated with a significantly lower dislocation rate compared with conventional THA (OR 0.26; 95% CI, 0.08 to 0.79); this was also confirmed by Romagnoli M. et al [ 32 ], who showed a slight significant risk ratio of 0.16 (95% CI, 0.09, 0.28; I 2 = 0%, p -value < 0.00001), with a statistically significant difference between the two groups.…”
Section: Discussionmentioning
confidence: 59%
“…Literature [27][28][29][30] has shown the superiority of DMTHR for fracture neck of femur in reducing dislocation rates and requirement of Revision arthroplasty compared to conventional THR. However, studies that have assessed the difference in functional outcome between the two implant designs are lacking.…”
Section: Introductionmentioning
confidence: 99%
“…Dual mobility components offer a possible solution to cases with high risk of dislocation. A systematic review of 23 studies showed that arthroplasties with dual mobility cups had significantly lower dislocation rates than patients treated with conventional THA (OR 0.26; 95%CI: 0.08 to 0.79) and hemiarthroplasty (OR 0.27; 95% 0.15 to 0.50), without increasing other complications [177]. Future prospective studies like the DUALITY register-based randomized controlled trial [178] and cost-analysis and studies are required to fully assess the potential benefit of this type of arthroplasty.…”
Section: Intracapuslar Hip Fracturesmentioning
confidence: 99%